Papiri - Clauser, Marina (Firenze University Press, 2009)
The word "papyrus" indicates both the plant and the resulting material used in ancient times for writing. The volume broadly traces the botanical and ecological characteristics of the plant, with notes on its technological use and its representation in art; it continues with references to writing, the history of the writing medium, papyrus plants and proto-papers, and ends with a reflection on the sustainable use of paper materials and on the differentiation of waste and recycling.